2021
DOI: 10.5713/ajas.19.0989
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in the coding region of the toll-like receptor 4 gene affects milk traits in Barki sheep

Abstract: Objective: Milk production is one of the most desirable traits in livestock. Recently, the toll-like receptor (TLR) has been identified as a candidate gene for milk traits in cows. So far, there is no information concerning the contribution of this gene in milk traits in sheep. This study was designed to investigate the <i>TLR 4</i> gene polymorphisms in Barki ewes in Egypt and then correlate that with milk traits in order to identify potential single nucleotide polymorphisms (SNPs) for these trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…No SNPs were reported in TLR4 exon2 of river buffalo breeds except in the study byTantia et al (2012) who reported a single SNP at position 1341nt. These Genetic variations between breeds of buffaloes can be attributed to environmental and/or genetic factors.The relative high frequency of non-synonymous SNPs in TLR4 detected in the present study was also reported in 11 different cattle breeds(White et al 2003); in Barki sheep(Sallam 2021), and Murrah buffalo (Roldan-Montes et al 2020) is justi ed since the TLR4 gene is a cell-surface pattern-recognition receptor important to recognition of a broad of PAMPs.It is worth mentioning that the reported three SNPs in the putative binding sites of TLR4 promotor region SNP c.1-g 27,. c1.-g.149 and c1.-g.150 has been previously reported in bovine promoter of TLR4 genes {Sharma et al 2006; Wang et al 2009; Mishra et al 2018 ) and in human and mouse TLR4 gene(Rehli et al 2000).…”
supporting
confidence: 83%
“…No SNPs were reported in TLR4 exon2 of river buffalo breeds except in the study byTantia et al (2012) who reported a single SNP at position 1341nt. These Genetic variations between breeds of buffaloes can be attributed to environmental and/or genetic factors.The relative high frequency of non-synonymous SNPs in TLR4 detected in the present study was also reported in 11 different cattle breeds(White et al 2003); in Barki sheep(Sallam 2021), and Murrah buffalo (Roldan-Montes et al 2020) is justi ed since the TLR4 gene is a cell-surface pattern-recognition receptor important to recognition of a broad of PAMPs.It is worth mentioning that the reported three SNPs in the putative binding sites of TLR4 promotor region SNP c.1-g 27,. c1.-g.149 and c1.-g.150 has been previously reported in bovine promoter of TLR4 genes {Sharma et al 2006; Wang et al 2009; Mishra et al 2018 ) and in human and mouse TLR4 gene(Rehli et al 2000).…”
supporting
confidence: 83%
“…Abousoliman (2021) carried out a genome-wide association study in the Egyptian Burki sheep breed and identified genomic regions in the important genes ABHD5, TBC1D1, KLF3, NUB1, and SLC5A8 for milk yield and other important regions in the genes FBLN1 and PPARA related to milk quality traits. Furthermore, Sallam (2021) identified a significant missense mutation rs592076818 in the TLR4 gene and concluded that the TLR4 gene can serve as a target for improving milk yield and milk quality characteristics in sheep worldwide. Sutera (Sutera et al 2021) found significant SNPs related to fat yield, protein percentage, and milk yield the SNP were identified in the OAR region of the chromosomes 2, 3, and 20 of the Valle del Sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on their type, mutations may affect transcription, translation, and mRNA transportation (Goymer, 2007). Conversely, missense mutations can damage the protein, make it nonfunctional (Minde et al, 2011), or sometimes enhance its action, indicating that they are beneficial to the animal as a whole (Sallam, 2021).…”
Section: Discussionmentioning
confidence: 99%